Impact of dry eye disease treatment on patient quality of life - Lin, Cheng-Wei; Lin, Meng-Yin; Huang, Jin-Wei; Wang, Tsung-Jen; Lin, I-Chan (Frontiers in Medicine, 2024)
Dry eye disease (DED) is a common multifactorial disease affecting a substantial proportion of the population worldwide. Objective tests and subjective symptoms evaluation are necessary to assess DED. Although various treatments have been introduced, accurately evaluating the efficacy of those treatments is difficult because of the disparity between diagnostic tests and patient-reported symptoms. We reviewed the questionnaires used to evaluate DED and the improvements of quality of life with various treatments. In addition, we highlighted the importance of patient-reported outcomes (PRO) assessments for evaluating the effect of DED treatments. Given that the assessment of DED treatment effectiveness substantially relies on individual ocular experiences, acquiring qualitative PRO data is essential for comprehensive evaluation and optimal treatment management. Clinicians should not only focus on improving objective symptoms but also prioritize the well-being of patients in clinical management.